Development of Ethnoscience Project-Based Worksheets "Jidor Art" for PGSD Students - Achmad Fanani; Rosmiati; Triman Juniarso; Feny Rita Fiantika (Jurnal Penelitian Pendidikan IPA, 2024)
Natural science and ethnoscience can help combine local knowledge with modern scientific knowledge to overcome problems in learning. The aim of this research is to determine the feasibility of a worksheet based on the "Jidor art" ethnoscience project for PGSD students, as well as to determine student responses in learning the Physics of sound concept course through a project assignment integrating the Jidor art ethnoscience approach. The subject used is the tanjidor musical instrument. The research method used is the development of the Borg and Gall R & D Model. From data collection to large group operational validation (Step 8). The feasibility results obtained an average score of 4.1 in the good category. Student responses stated that 69.75% agreed that it was acceptable. Thus, it can be concluded that the worksheet based on the ethnoscience project "Jidor Art" for PGSD students is declared suitable for use. Student responses stated that they agreed that it could provide insight, challenge, make things easier and fun, as well as foster the 4C.